Traços de didaticidade em artigos de divulgação científica mediática : O caso de uma edição especial “verde” da revista Visão - Ramos, Rui (2017)
Since 2007, on an annual basis, the weekly general information magazine Visãopublishes a “green” edition, dedicated to environmental issues.This study examines the occurrence and functions of reformulation mechanisms identifiable in the texts or textual segments of science popularization present in the 2014 and 2015 editions of this magazine. Firstly, it elaborates on the hypothesis that genre characteristics of the analysed discourse (thediscourse of public communication of science through the media) favour their occurrence at the service of referenciation and that they have implications for the construction of the image of the interlocutors, and also for the interlocutive relationships established in / by text/discourse.Secondly, the study considers the texts under analysis marked by weak didacticity, which de- rived primarily from the communicative situation and from the communicative goals the texts have. It also recognizes the importance that the discourse of science (in its popularization fea- ture) assumes relating to the theme in question and the textual organization adopted.The consideration of global data suggests that the reformulation is present without being a cen- tral feature. The reformulation markers are identifiable and they are productive. However, most reformulation operations occur without any reformulation discourse markers.